Kajian Dan Interkoneksi Manajemen Pendidikan Islam Terhadap Poleksosbud Di Indonesia - Supriadi, Supriadi; Isma, As'ad; Jamrizal, Jamrizal (El-Ghiroh : Jurnal Studi Keislaman, 2023)
In the backdrop of Indonesia's diverse poleksosbud landscape, the management of Islamic education stands out as a significant factor influencing the nation's fabric. This research was embarked upon with the objective of elucidating the interrelation between Islamic education management and the political, economic, social, and cultural dimensions in Indonesia. A qualitative research approach was chosen, primarily focusing on a literature review to draw insights. The findings revealed that the management of Islamic educational institutions both impacts and is reciprocally influenced by the prevailing poleksosbud conditions. Effective management of these institutions can foster a harmonious integration of these dimensions, thereby contributing to the holistic development of the nation. It's concluded that a balanced appreciation and application of Islamic education management principles are essential for the prosperous and cohesive growth of Indonesian society.